Educational recommendations for the conduct, content and format of EULAR musculoskeletal ultrasound Teaching the Teachers Courses. Issue 1 (6th October 2015) - Iagnocco, A; Terslev, L; Backhaus, M; Balint, P; Bruyn, G A W; Damjanov, N; Filippucci, E; Hammer, H B; Jousse-Joulin, S; Kane, D; Koski, J M; Mandl, P; et al.
Abstract : Objective: To produce educational guidelines for the conduct, content and format of theoretical and practical teaching at EULAR musculoskeletal ultrasound (MSUS) Teaching the Teachers (TTT) Courses. Methods: A Delphi-based procedure with 24 recommendations covering five main areas (Duration and place of the course; Faculty members; Content of the course; Evaluation of the teaching skills; TTT competency assessment) was distributed among a group of experts involved in MSUS teaching, in addition to an advisory educational expert being present. Consensus for each recommendation was considered achieved when the percentage of agreement was >75%. Results: 21 of 24 invited participants responded to the first Delphi questionnaire (88% response rate). All 21 participants also responded to the second round. Agreement on 19 statements was obtained after two rounds. Conclusions: This project has led to the development of guidelines for the conduct, content and format of teaching at the EULAR MSUS TTT Courses that are organised annually, with the aim of training future teachers of EULAR MSUS Courses, EULAR Endorsed MSUS Courses, as well as national and local MSUS Courses. The presented work gives indications on how to homogenise the teaching at the MSUS TTT Courses, thus resolving current discrepancies in the field.